Endoscopic therapies for the prevention and treatment of early esophageal neoplasia. (November 2011) - Green, Susi; Bhandari, Pradeep; DeCaestecker, John; Barr, Hugh; Ragunath, Krish; Jankowski, Janusz; Singh, Rajvinder; Longcroft-Wheaton, Gaius; Bennett, Cathy
Esophageal cancers have traditionally been diagnosed late and prognosis has been dire. For many years the only real treatment option was esophagectomy with substantial morbidity and mortality. This situation has now changed dramatically. Improvements have been achieved in surgical outcomes and there is an array of new effective treatment options now available, particularly for the increasing proportion diagnosed with early-stage disease. Minimally invasive endoscopic therapies can now prevent, cure or palliate esophageal cancers. This article aims to investigate the role and evidence base for these new therapeutic options.